PENGARUH SISTEM AKUNTANSI MANAJEMEN, STRATEGI BISNIS DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJERIAL - Sarah Kamilah; Zaldy Suhatman (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine the influence of management accounting systems, business strategies, and environmental uncertainty on managerial performance at PT. BRM. The dependent variable in this study is managerial performance, while the independent variables are management accounting systems, business strategies, and environmental uncertainty. This study uses a quantitative method with primary data obtained through questionnaires distributed to office staff at PT. BRM. The population consists of 116 employees, and the sample of 56 respondents was selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 30.0. The results show that all three independent variables simultaneously and partially influence managerial performance.